Does Metabolic Syndrome Impair Sexual Functioning in Adults With Overweight and Obesity?. Issue 2 (3rd April 2019) - Botlani Esfahani, Saeideh; Pal, Sebely
Abstract: Objectives: Obesity is a growing public health concern worldwide, and results in increased risk of cardiovascular disease, type 2 diabetes, metabolic syndrome, insulin resistance, dyslipidemia, hypertension, and reduced sex hormone production. Previous research suggests that obesity may contribute to sexual dysfunction. This review aims to determine the relationship between obesity and sexual dysfunction, and ascertain the associated cardiometabolic conditions that may contribute to impaired sexual functioning in individuals with obesity. Methods: Literature searches were conducted through PubMed and Embase from 1980 to 2016, to identify original research articles, reviews including systematic reviews and meta-analyses, using the search terms: obese, obesity, overweight, sexual function, sexual dysfunction, metabolic syndrome, CVD, T2D, hormones and weight loss. Results: This review found that individuals with obesity and cardiometabolic comorbidities were more likely to report the greatest degree or sexual dysfunction and/or reduction in sexual quality of life, compared to those without. Conclusions: Current evidence supports an association between sexual dysfunction and factors associated with obesity, such as reduced insulin sensitivity, dyslipidaemia, hypertension, and low oestrogen or testosterone. To establish efficacious treatments, research examining the impact of weight loss on the conditions associated with obesity, such as hypertension, reduced insulin sensitivity, dyslipidaemia, and low sex hormones and sexual functioning in individuals with overweight and obesity should be a priority.